2019
DOI: 10.1002/adfm.201902673
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Functional Photosensitizer for Ultraefficient Photodynamic Therapy and Synchronous Anticancer Efficacy Monitoring

Abstract: A dual-functional photosensitizer that demonstrates exceptional photodynamic therapy (PDT) efficacy while simultaneously self-monitoring the therapeutic response in real time is reported here. Possessing an ultrahigh 1 O 2 quantum yield of 98.6% in water, the photosensitizer TPCI can efficiently induce cell death in a series of carcinoma cells (IC 50 values less than 300 × 10 −9 m) upon irradiation with an extremely low fluence (460 nm, 4 mW cm −2 for 10 min). In addition, TPCI can self-monitor cell death in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 53 publications
3
97
0
Order By: Relevance
“…Recently, two AIEactive PSs were developed with self-monitoring ability, which could translocate from mitochondria to the nucleus and bind with nucleic acids during PDT treatment. 33,34 However, their ultimate binding with nucleic acids may lead to genotoxic, carcinogenic, and teratogenic risks. 35 To endow the AIE-active PSs with a safe self-monitoring ability, we herein develop an AIE-active PS, TTVPHE, which could not only efficiently destroy the mitochondria in cancer cells, but also in situ monitor the therapeutic process by translocating from the damaged mitochondria to the nuclear membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two AIEactive PSs were developed with self-monitoring ability, which could translocate from mitochondria to the nucleus and bind with nucleic acids during PDT treatment. 33,34 However, their ultimate binding with nucleic acids may lead to genotoxic, carcinogenic, and teratogenic risks. 35 To endow the AIE-active PSs with a safe self-monitoring ability, we herein develop an AIE-active PS, TTVPHE, which could not only efficiently destroy the mitochondria in cancer cells, but also in situ monitor the therapeutic process by translocating from the damaged mitochondria to the nuclear membrane.…”
Section: Introductionmentioning
confidence: 99%
“…As presented in Table S1, † the large extinction coefficient (3 Â 10 4 ) and small DE ST values were favorable for ROS generation, and a large stoke-shi (140 nm) as exhibited in Fig. S33a-e and S34 † indicated their great potential for imagingguided PDT [50][51][52][53] In vitro ROS generation c would subsequently trigger a series of synergetic cascade reactions ( Fig. 1e), yielding more toxic ROS.…”
Section: Molecular Design and Basic Photophysical Propertiesmentioning
confidence: 95%
“…Recently, Zhang et al presented a self‐reporting strategy that could be achieved by monitoring apoptosis during PDT in situ, which utilized the translocation of PS (TPE‐4EP+) from mitochondria to the nucleus. Gao et al reported another photosensitizer (TPCI), which was weakly fluorescent in living cells in the absence of irradiating light but showed enhanced emission from nuclei during PDT treatment ( Figure A). This was used for self‐reporting cell death during PDT in real time, as indicated by the excellent colocalization of TPCI and propidium iodide (PI) (Figure B).…”
Section: Image‐guided Therapymentioning
confidence: 99%
“…C) Changes in tumor size (dashed black circles) at different times in a B16F10 melanoma‐bearing mouse model. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: Image‐guided Therapymentioning
confidence: 99%